Vulnerabilidade socioespacial de corpos dissidentes: lugar referencial de acolhimento à mulher em Sorocaba - SP - Souza, Gleicielly Oliveira de (Universidade Federal de São Carlos, 2022)
The present Course Conclusion Work aims to approach the scale scale of Raul Borges Guimarães, conception of the scale of the body, which are differentiated depending on their specificities, developing identities and resistances against the oppression that socially and spatially were instituted on these bodies, becoming social bodies, we link this conception of the scale of the body with the concepts of place with the perspective of the geographer Milton Santos who interprets the relationship of the local/global, emphasizing the temporality of each place or a social time by groups or individuals. The current work comes with the proposal to think about the gender identity of women, with the racial cuts of white, black and non-white women who suffer violence in different ways because they start from different historical perspectives, for the understanding of place and non-place we link Doreen Massey's concept of spatiality. We try to relate the construction of gender identity with the social construction of Judith Butler and Paul Preciado to understand the violence against corporeities that identify themselves as women. The theme of socio-spatial violence had as an analysis scale the CEREM which is located in the city of Sorocaba-SP, we interviewed two CEREM employees who care for women in situations of violence, the first is a psychologist who works in the technical area of care for women and the second interviewee is a social worker who specializes in listening to domestic violence.
Sociospatial vulnerability of dissident bodies: place reference for welcoming women in Sorocaba - SP
Keywords: Lugar; Mulher; Corpo; Violência Socioespacial; Place; Woman; Body; Sociospatial Violence; CIENCIAS HUMANAS::GEOGRAFIA::GEOGRAFIA HUMANA